The young HD 73583 (TOI-560) planetary system: two 10-M⊕ mini-Neptunes transiting a 500-Myr-old, bright, and active K dwarf. Issue 2 (15th March 2022) - Barragán, O; Armstrong, D J; Gandolfi, D; Carleo, I; Vidotto, A A; Villarreal D'Angelo, C; Oklopčić, A; Isaacson, H; Oddo, D; Collins, K; Fridlund, M; Sousa, S G; et al.
ABSTRACT: We present the discovery and characterization of two transiting planets observed by TESS in the light curves of the young and bright ( V  = 9.67) star HD73583 (TOI-560). We perform an intensive spectroscopic and photometric space- and ground-based follow-up in order to confirm and characterize the system. We found that HD73583 is a young (∼500 Myr) active star with a rotational period of 12.08 ± 0.11  d, and a mass and radius of 0.73 ± 0.02 M⊙ and 0.65 ± 0.02 R⊙, respectively. HD 73583 b ( Pb  = $6.3980420 _{ - 0.0000062 } ^ { + 0.0000067 }$  d) has a mass and radius of $10.2 _{ - 3.1 } ^ { + 3.4 }$   M ⊕ and 2.79 ± 0.10  R ⊕, respectively, which gives a density of $2.58 _{ - 0.81 } ^ { + 0.95 }$  ${\rm g\, cm^{-3}}$ . HD 73583 c ( Pc  = $18.87974 _{ - 0.00074 } ^ { + 0.00086 }$  d) has a mass and radius of $9.7 _{ - 1.7 } ^ { + 1.8 }$   M ⊕ and $2.39 _{ - 0.09 } ^ { + 0.10 }$   R ⊕, respectively, which translates to a density of $3.88 _{ - 0.80 } ^ { + 0.91 }$  ${\rm g\, cm^{-3}}$ . Both planets are consistent with worlds made of a solid core surrounded by a volatile envelope. Because of their youth and host star brightness, they both are excellent candidates to perform transmission spectroscopy studies. We expect ongoing atmospheric mass-loss for both planets caused by stellar irradiation. We estimate that the detection of evaporating signatures on H and He would be challenging, but doable with present and future instruments.